PENGARUH PEREBUSAN PADA IMPREGNASI KAYU KARET - Harly Harly (Jurnal Penelitian Hasil Hutan, 1990)
Rubberwood  is  becoming more important in  Indonesia and  hence research for   better treatment of  this  very susceptible wood  species  is badly needed. In general, the impregnation  of  the green wood  results in a limited  penetration.Boiling before preservative treatment by alternating pressure process greatly  improved  the  treatment of rubberwood. A boiling period  for one hour was sufficient to obtain  required penetration  of preservative.